Development of a survey tool to assess emotional and social behavioral competencies of science technology engineering math and medicine (STEMM) graduate students - Joann Farrell Quinn; Philip A. Cola; Melissa Cooper; Casey Miller (PLoS ONE, 2025)
The underrepresentation of women and minority students in STEMM graduate programs remain a significant challenge, compounded by biases in traditional admissions processes and barriers to effective mentoring and retention. This study develops and validates the Quinn Miller Competency Assessment (QMCA), a tool designed to assess emotional and social intelligence (ESI) competencies crucial for STEMM graduate student success. The QMCA was created through an iterative process involving literature review, expert consultations, and empirical studies. It evaluates five key competencies: self-awareness, self-control, adaptability, achievement orientation, and teamwork. The tool’s validity and reliability were tested using exploratory and confirmatory factor analyses on diverse samples of STEMM graduate students and applicants. Results demonstrated strong construct validity and reliability and invariance across gender and race/ethnicity supporting the QMCA’s use in both admissions and student development contexts, in conjunction with other measures. By enabling a more holistic evaluation of applicants’ competencies through an assessment that fairly and consistently evaluates individuals across demographic groups, the QMCA aims to improve access and retention for underrepresented groups in STEMM fields, fostering a more inclusive and diverse scientific community. Future research will specifically explore how the QMCA can enhance holistic evaluation processes and contribute to student retention and success efforts. Additionally, we will test its applicability across broader disciplines.